2016
DOI: 10.1038/ctg.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Immunochemical Tests Combined With Other Stool Tests for Colorectal Cancer and Advanced Adenoma Detection: A Systematic Review

Abstract: OBJECTIVES:Despite moderate to high detection rates of fecal immunochemical tests (FITs) of colorectal cancer (CRC), detection of adenomas remains limited. Further stool tests exist, which are not used in routine practice, such as DNA or RNA markers and protein markers. We aimed at systematically investigating and summarizing evidence for diagnostic performance of combinations of FIT with other stool tests compared with FIT alone in early detection of CRC and its precursors.METHODS:We systematically reviewed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(94 reference statements)
1
10
0
1
Order By: Relevance
“…In screening practice, instead of simply applying and strictly sticking to the threshold value recommended by the manufacturer the advantage of quantitative FITs regarding the flexibility for threshold adjustments should be extensively exploited to adjust the threshold value to yield a desired PR (which is a very good proxy indicator for the specificity). Niedermaier et al 50 reviewed the diagnostic performances of FITs in combination with other fecal-based markers until 2015 and came to the conclusion that some combinations might have the potential to improve the diagnostic performance of FITs, but further evaluations in true screening settings are necessary. Such a threshold adjustment has recently been made, for example, in the FIT-based screening program of the Netherlands, where the initial threshold of 15 mg Hb/g feces of FOB Gold was later increased to 47 mg Hb/g feces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In screening practice, instead of simply applying and strictly sticking to the threshold value recommended by the manufacturer the advantage of quantitative FITs regarding the flexibility for threshold adjustments should be extensively exploited to adjust the threshold value to yield a desired PR (which is a very good proxy indicator for the specificity). Niedermaier et al 50 reviewed the diagnostic performances of FITs in combination with other fecal-based markers until 2015 and came to the conclusion that some combinations might have the potential to improve the diagnostic performance of FITs, but further evaluations in true screening settings are necessary. Such a threshold adjustment has recently been made, for example, in the FIT-based screening program of the Netherlands, where the initial threshold of 15 mg Hb/g feces of FOB Gold was later increased to 47 mg Hb/g feces.…”
Section: Discussionmentioning
confidence: 99%
“…Robertson et al 16 updated the dataset from Lee et al 17 until 2015 and also extracted sensitivity and specificity values for AA or AN, but did not include any meta-analyses or analyses of determinants of test performance. Niedermaier et al 50 reviewed the diagnostic performances of FITs in combination with other fecal-based markers until 2015 and came to the conclusion that some combinations might have the potential to improve the diagnostic performance of FITs, but further evaluations in true screening settings are necessary. We have summarized the diagnostic performance of quantitative FITs at multiple threshold values for CRC, AA and their combination, AN, exclusively focusing on studies conducted in screening settings with colonoscopy as the reference (gold-)standard among all participants.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] However, to improve the sensitivity of FITs, especially for the detection of premalignant lesions of CRC, new approaches like the combination of FITs with other stool-based markers are under investigation. 13 Previous studies suggested that combining FITs for hemoglobin with fecal transferrin might increase sensitivity among symptomatic individuals. [14][15][16] For example, Sheng et al reported an increase of sensitivity for CRC and advanced adenoma (AA) from 75% to 90% and from 44% to 78%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, to improve the sensitivity of FITs, especially for the detection of premalignant lesions of CRC, new approaches like the combination of FITs with other stool‐based markers are under investigation 13 . Previous studies suggested that combining FITs for hemoglobin with fecal transferrin might increase sensitivity among symptomatic individuals 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…La tasa de detección de adenomas avanzados (TDAa) expresa probablemente un resultado más importante y transcendente que los adenomas en general, debido al número y tamaño de las lesiones y su mayor riesgo de situación avanzada. En el grupo de exposición la TDAa es muy alta (49,1%) comparada con la bibliografía existente (159), y comparada con el grupo control (36%), lo que indica que la intervención es realmente importante para el futuro de estos pacientes por el descenso esperado del riesgo de desarrollar un CCR. Además, la tasa de adenomas avanzados en nuestro estudio se acerca en muchos casos a tasas de adenomas no avanzados de múltiples estudios.…”
Section: Tasa De Detección De Adenomas Y Adenomas Avanzadosunclassified